Screening of phytochemicals and antimicrobial activity of some seaweeds from the east coast of Tripoli, Libya - Elmansori, Abdalla A.; Alghazeer, Rabia; Saadi, Mohammed (المؤتمر العلمي الثاني لعلوم البيئة، 2015م, 2015)
In this study, crude methanolic extracts of six algal species, two chlorophyta Enteromorpha linza and Codium tomentosum , three phaeophyta Padina pavonica ,Sargassum vulgare and Cytociera sp. and one rhodophyta Gelidium sesquipedale, collected from the east coast of Tripoli, were evaluated for antimicrobial activity against four species of bacteria, two gram positive Staphylococcus aureus and Bacillus subtilis and two gram negative Escherichia coli and Salmonella typhi , and two fungal species Aspergillus sp. and Penicillum sp.. Most of the extracts showed a significant antimicrobial against all four bacteria species. Among tested algae, green algae namely Enteromorpha linza exhibited the highest antibacterial activity, meanwhile the most effective algal extract against the two fungal species was the red algae Gelidium sesquipedale. The study showed that the residual content of the dry matter of these algal samples were varied andthe highest was obtained from the brown algae S. vulgare .